Predictor Factors Affecting the Use of Implants Contraceptives by Reproductive Age Couples - Ni Putu Wiwin Sofi Martyanti; Ni Wayan Suarniti; Ni Komang Yuni Rahyani (Universitas Muhammadiyah Semarang, 2024)
The World Health Organization (WHO) reports an increase in contraceptive use in various parts of the world. However, the use of contraceptive implants is still the lowest, at only 7.3%. In Indonesia, the use of Long-Term Contraceptive Methods (MKJP), including implants, is still lower than the use of non-MKJP. Preliminary study at UPTD. The Klungkung I Community Health Center shows that there are still many couples of childbearing age (PUS) who have not used contraception, namely 47.62%. This study aims to determine the factors associated with PUS participation in the use of implantable contraceptives in the UPTD in the working area of Klungkung I Community Health Center. The type of research is analytical observational with a cross-sectional approach. The sample size was 54 respondents. The results of the study using the Fisher-exact test showed the characteristics of parity p<0.05, husband's support p<0.05, and knowledge p<0.05. The conclusion of this research is that there is a relationship between parity, husband's support, and knowledge with the participation of couples of childbearing age in the use of contraceptive implants in the UPTD work area. Klungkung I Community Health Center.